Implications of Islamic Law in Business Dispute Resolution: A Qualitative Approach to Muslim Entrepreneurs - Evra Willya (Sanskara Hukum dan HAM, 2023)
This research study explores the implications of Islamic law (Sharia) in the settlement of business disputes among Muslim entrepreneurs in West Java, Indonesia. Using a qualitative research approach, this study explores how Islamic principles are integrated into decision-making processes and conflict resolution strategies. Through thematic analysis of the interviews, this study uncovers themes of ethical integration, peaceful resolution through mediation (Sulh), the mediating role of religious principles, and the challenge of harmonizing Sharia with the legal system. These findings contribute to an understanding of the interaction between Islamic values and modern business practices, providing insight into ethical considerations and cultural sensitivity in dispute resolution.